Analisis Kualitas Aplikasi KAI Access Menggunakan Model ISO 25010 - Rahman, Ambia; Aviarini Indrati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
The increasing usage time of smartphones can encourage application development in various fields including transportation. Advances in internet technology and software have made the ticket purchasing process easier for the public. The KAI Access application allows consumers to book and purchase train tickets and view train departure schedules easily and efficiently. This application is an application that has been downloaded as many as 10 million downloads on Google Playstore but received a poor assessment. The ISO 25010 model can be used as a reference to ensure that software can meet good quality standards. This study aims to analyze the quality of the KAI Access application using the ISO 25010 method and provide recommendations for the development design of the KAI Access application based on the analysis results. This test uses 4 of the 8 ISO 25010 characteristics, namely Functional Suitability, Performance Efficiency, Usability, and Reliability. Application testing is carried out on 3 different devices using Blackbox Testing, Stress Testing, and Questionnaires. The suggestions for adding features from other KAI Access users are such as adding Go Show tickets, an easier refund process, and adding payment options. After conducting a series of tests on the application, it was found that testing the KAI Access Application with the ISO 25010 method from 4 characteristics got a result of 4.54 which means good